A Systematic Kinetic Study of Oxidation of o-Toluidine by Chromic Acid - Singh, Ranveer (Asian Journal of Chemistry, 2010)
The rate of oxidation of o-toluidine by chromic acid have been measured in acetic acid-water medium. The orders in oxidant, substrate and H+ have been obtained one in each. The effect of neutral salts, catalysts, solvent polarity and temperature on the rate of oxidation have been studied. A suitable mechanism consistent with the experimental results has been proposed.